Social media (chocodictive jar) / Shazatul Nazha Zaiman - Zaiman, Shazatul Nazha (2019)
Chocodictive Jar offers choco jars products and services that are more likely to meet customer needs. This is because innovation allows the business to be updated with the latest changes in tastes and preferences of the consumers and hence, to serve those preferences and increase its profits. v The uniqueness of this product is the ingredients. I used the quality chocolate which is Beryl's to melt it together with quality the bubble rice to maintain its crispiness. It also comes with variety of toppings which most of them are from well-known brands such as Kinder Bueno, M&M, Kit Kat, Toblerone, Daim, and Oreo Mini. In addition, I have 'sigrjature'^topping which is almonds and it classified under 'signature' because it is the different to be compared to other choco jar business. Chocodictive Jars' customers are obviously from chocolate lovers who are from kids, teenagers, couples and etc. It also suitable to be given as a gift to someone. In Putrajaya, there are few competitors such as Choco Belle, Chocojar licious and Chocodbury jar. However, Chocodictive Jar beneficial to be compared to other competitors is because of the variety of topping with affordable price. It also have the 'signature' almonds topping while they're not. The management of Chocodictive Jar consists of two workers which are Shazatul Nazha Binti Zaiman and my mother, Norlin Binti Adam. I also create Facebook to expand my business through social media and learn how to post Facebook post for business product. Furthermore, to be easier, I signed my business up in eUsahawan portal to track my business for profits and revenues occurred. V \ For now, I have product and service commitment plan to promote the product. I can do both for postage and delivery for customers. However, there are still have the selected area to delivery which are Putrajaya, Kajang, Bangi, Cyberjaya and Cheras.